2020
DOI: 10.5334/bc.53
|View full text |Cite
|
Sign up to set email alerts
|

Preparing ‘middle actors’ to deliver zero-carbon building transitions

Abstract: The urgent transition to a zero-carbon economy requires building professionals to be supportive of, and prepared for, delivering zero-carbon buildings. Building professionals are important 'middle actors' who can either enable or inhibit such societal transitions. This paper explores building professionals' perspectives on delivering zero-carbon buildings, leading to a practical synthesis of knowledge and skill requirements and training pathways. It draws on the middle-out perspective (MOP) and secondary analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The urban design process is highly complicated, involving many actors, engaging with multiple contending forces, with highly intricate interactions between all these. It is this complexity which Figure 5 seeks to depict [177,178]. As a result, there is no single paramount paradigm around which to organize thought and action in this arena.…”
Section: Discussionmentioning
confidence: 99%
“…The urban design process is highly complicated, involving many actors, engaging with multiple contending forces, with highly intricate interactions between all these. It is this complexity which Figure 5 seeks to depict [177,178]. As a result, there is no single paramount paradigm around which to organize thought and action in this arena.…”
Section: Discussionmentioning
confidence: 99%
“…Similar concerns have been found previously, with building professionals being reluctant to recommend technologies that may not be cost effective. 42 The main example of suggesting insulation in our data was when to accompany a heat pump, which requires well insulated homes to operate effectively, and as the pumps are relatively expensive, the additional cost of insulation was viewed as being more proportionate. Installer confidence appears to be a success criterion for retrofit products; this may have implications for products other than IWI.…”
Section: Discussionmentioning
confidence: 94%
“…An obvious limitation is the small sample size, partly occasioned by the exploratory nature of the study, and the deliberate selection of experts in two sub-sectors, making a smaller pool inevitable with the resources and time available. Although other studies in this area of research have had successful results with similar interview sample sizes [49,59,67,68], future research would benefit from investigating these initial exploratory findings amongst a wider selection of interviewees. Additionally, in some cases, respondent organisations are "pro-environmental", which may introduce a positive bias towards the adoption of low-carbon strategies and technologies.…”
Section: Limitationsmentioning
confidence: 97%
“…They use Janda and Parag's ideas to suggest that tensions between micro (on the job "real work" by individuals) and macro (institutional change at a larger scale) are worthy of further investigation when considering professionals' role in environmental change. More recently, Simpson et al [59] found that middle actors-in this case, tradespeople in the building industry-do not have equal ability to influence policymakers upstream and clients downstream. Their downstream influence was greater than their upstream influence.…”
Section: Middle Actors and The Middle-out Perspectivementioning
confidence: 99%